INVESTIGATING SECONDARY SCHOOL STUDENTS’ ANXIETY LEVEL IN ENGLISH EXAMINATION - Novinda Rosayanti; Miftahul Mahrus (English Education Department, 2021)
The preliminary research showed that students at the eleventh grade of State Senior High School 2 Enok had anxiety in the English examination. It can be seen that some of the students were confused in the English examination because the students got anxious. This research aimed to investigate the students’ anxiety in English examination at the eleventh grade of State Senior High School 2 Enok. Descriptive research is employed as the design. The population of the research was the students at the eleventh grade of state senior high school 2 Enok. The number of samples was selected by using a technique called simple random sampling. The sample was 30 students. The researchers obtained the data from the questionnaire. The data were analyzed by using descriptive statistics calculated by SPSS 20.0 program. The findings showed that the majority of students’ anxiety at the eleventh grade of State Senior High School 2 Enok was mediocre with 66.67%. Some of them were at a low level with 33.33%. While 0% in a high level. Thus, based on the data obtained it could be concluded that the students still have anxiety in English examination even at the mediocre level.